String Gas Cosmology: Basics and Brandenberger-Vafa Scenario - Năstase, Horaţiu [UNESP] (My University, 2019)
In this chapter we address the first truly stringy cosmological model, the string gas model, started by Brandenberger and Vafa. The reason for the model starts with a very simple observation: If inflation lasts for more than 70 e-folds (which admittedly is not necessary, we need more than 50–60 e-folds, but restricting Ne< 70 would not be needed for experimental reasons, only for calculational reasons, which seems unreasonable), then current cosmological scales, ∼H0-1, that leave an imprint in the CMBR, were less than Planck size lPl at the initial time. But then we cannot trust the effective field theory of inflation, and we would need a full quantum gravity theory, like string theory.